EFFICACY OF RIBOSOMAL COMPLEX IN EPSTEIN–BARR VIRAL INFECTION IN CHILDREN - S.N. Orlova; S.A. Mashin; S.V. Zhambarov (Вопросы современной педиатрии, 2011)
Article contains study results of clinical efficacy of ribomunil in complex treatment and rehabilitation program in 30 children, recovered from acute Epstein–Barr viral infection, with disbiosis of nasal, oropharyngeal and colon mucosa. It has been shown that application of ribosomal complex over 1 to 6 months allows successful sanitization of main body loci, it also promotes normalization of blood parametres, decrease general sensitization of the body and thus prevent Epstein–Barr viral infection from becoming chronic and decrease the amount of intercurrent diseases in children.Key words: Epstein–Barr viral infection, disbiosis of main body loci, ribomunil, children. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 41–47.)